2014
DOI: 10.17509/bs_jpbsp.v14i2.719
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Speaking Self-Efficacy and Gender in Speaking Activities

Abstract: The present study tries to find out the effect of speaking self-efficacy and gender

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…This material contains oral communication activities to help students achieve confidence and become effective speakers to many types of communications challenges both formal and informal gatherings (Romano, 1994). Each activity is designed to help participants better understand some facet of communications and gain expertise and proficiency in communication (Hanna Sundari & Dasmo, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This material contains oral communication activities to help students achieve confidence and become effective speakers to many types of communications challenges both formal and informal gatherings (Romano, 1994). Each activity is designed to help participants better understand some facet of communications and gain expertise and proficiency in communication (Hanna Sundari & Dasmo, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The difference also occurs in the variable of self-efficacy. The result of the earlier research showed that self-efficacy did not affect the speaking activities of the students (Sundari & Dasmo, 2014); but the later study proved that the correlation between self-efficacy and the performance of the students in speaking skills was significant (Sari, 2016). Therefore, in this current research, the researcher wanted to find out the correlation between the usage of multimedia in the academic context and the speaking performance of engineering students at Sriwijaya State Polytechnic.…”
Section: Introductionmentioning
confidence: 91%
“…Some studies regarding the usage of multimedia and its correlation to academic achievement have been conducted by some researchers (Kiat et al, 2020;Mahdi, 2022;Setiawan & Phillipson, 2020;Shakil et al, 2020). The research regarding self-efficacy and its influence on academic attainment have also been discussed (Meral et al, 2012;Musyarrafah & Korompot, 2022;Sari, 2016;Sundari & Dasmo, 2014). Unfortunately, the literature regarding the contribution of multimedia and selfefficacy on the speaking performance of the students was very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Ketika siswa diminta bercerita di depan kelas, siswa seringkali tidak mempunyai ide, malu, grogi sehingga kata yang diucapkan menjadi tersendat-sendat/diulang-ulang. Hal ini disebabkan oleh kesulitan siswa dalam praktik bercerita di antaranya karena faktor dalam diri siswa menjadi kurang jelas dan siswa kurang mampu mengorganisasikan perkataannya pada saat bercerita (Hanna Sundari & Dasmo, 2014;Lindblad, 2011). Dengan demikian, dapat diidentifikasi bahwa keterampilan bercerita siswa masih rendah.…”
Section: Pendahuluanunclassified